Stable Isotope Sclerochronology of Melanopsis (Gastropoda) Shells: Inferring Late Pleistocene Seasonality in the Upper Jordan River Valley - Rice, Addison, 1991- (2018)
Sub-weekly to sub-monthly records of δ 18 O and δ 13 C values in Melanopsis shells from the Jordan River Dureijat (JRD) archaeological site in the upper Jordan River Valley are assessed for changes in seasonal hydrology in the gastropod’s habitat, and these records are compared to results from one modern shell, collected from Agamon Hula. Growth marks which correspond with abrupt decreases in δ 18 O and δ 13 C values in the modern shell are interpreted as a pause in growth during the winter months. While the modern shell displays a large range of δ 18 O values and has a strong correlation between δ 18 O and δ 13 C values, fossil shells exhibit smaller ranges and weak or no correlation between δ 18 O and δ 13 C values, implying that the water body was hydrologically open. Mean δ 18 O values did not exhibit large changes among sedimentary layers (-6.8, -6.8, -7.3, -6.2‰ for layers dated 23.8, 18.6, 16.3, 14.5cal ka BP, respectively), and were remarkably similar to the modern shell mean δ 18 O (-6.4‰). A distinct difference between the δ 18 O and δ 13 C patterns from the different layers is observed. Shells dated to colder periods (23.8, 18.6cal ka BP) show little seasonality in δ 18 O and δ 13 C values, consistent with a large, buffered water body. Those dated to 16.3cal ka BP exhibit rapid changes which may reflect a stream environment, rather than a lake. Finally, shells dated to 14.5cal ka BP exhibit larger seasonal changes, perhaps due to a longer residence time. University of Iceland Research Fund, Rannsóknasjóður Háskóla Íslands; Erasmus+